Climate protection in mega-event greening: the 2010 FIFA™ World Cup and COP17/CMP7 experiences in Durban, South Africa. (7th August 2016) - Diederichs, Nicola; Roberts, Debra
Abstract : The implementation of 'event greening' initiatives that address the social, ecological, climate and legacy impacts of 'mega-events' is now accepted global practice. Since 2006, measuring, reporting and offsetting climate impacts have become central elements of such greening programmes. Without a standardized approach, however, host city governments and local environmental champions play a key role in determining the scope and scale of climate protection interventions, making comparisons between mega-events and host cities difficult. Recently, the city of Durban in South Africa was responsible for developing and implementing greening programmes for two mega-events: the Durban 2010 FIFA™ World Cup and the United Nations Framework Convention on Climate Change COP17/CMP7 in 2011. These experiences have highlighted the high cost of mitigating the climate impacts of mega-events, but also underscored the significant opportunities such events offer to promote investments in resource-efficient local infrastructure and to establish local climate protection projects that deliver long-term social and ecological co-benefits. The analysis of the ecological footprint of COP17/CMP7 also demonstrated that while climate protection has received substantial attention in mega-event greening, a broader set of global environmental change priorities need to shape the focus of future greening efforts.